The feather mites of nightjars (Ayes: Caprimulgidae), with descriptions of two new species from Brazil (Acari: Xolalgidae, Gabuciniidae) - Hernandes, Fabio Akashi (2014)
Two new species of feather mites are described from nightjars (Caprimulgiformes: Caprimulgidae) of Brazil: Hartingiella neotropica sp. n. (Xolalgidae) described from Hydropsalis parvula (Gould) and Paragabucinia brasiliensis sp. n. (Gabuciniidae) from H. albicollis (Gmelin). The former differs from the type species by having, in males, the anterior projections on epimerites III towards setae 3b and the adanal shield bearing setae ps3 present; in both sexes, a pair of small sclerites situated posterior to setae se have flat suprategumental processes. Paragabucinia brasiliensis sp. n. differs from P petitoti (Gaud et Mouchet, 1959) by the smaller size of the incisions in the internal margins of opisthosomal lobes of males. These mites are the first representatives of corresponding genera described from the Neotropical region. The genus Hartingiella Gaud, 1980 was previously known solely from its type species. Keys to males and females of the genus Paragabucinia Gaud et Atyeo, 1975 are presented. In addition, all previous records of feather mites associated with birds of the order Caprimulgiformes of the world are summarised.